Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I have a system of equations with two equations containing the Lambert $W$ function as follows,

$$\begin{cases} x = 1 - W_0(\frac{C_1 e^{y + 1}}{y + 1}) \\ y = 1 - W_0(\frac{C_2 e^{x + 1}}{x + 1}) \end{cases}$$

I have already solved the system numerically using a simple iterative method. A gentleman told me that the answer to the system is $y = \frac{k_1 - k_2 x}{k_1 x - k_2}$ where $k_1 = C_2 - C_1$ and $k_2 = C_2 - C_1$ but I have no clue how can one compute the answer.

  1. How can I get the answer to the system (i.e the steps)?
  2. While we have two curves in the system of equation, the intersection (i.e the answer of the system) must be a point not a curve. But $y = \frac{k_1 - k_2 x}{k_1 x - k_2}$ is a hyperbola. How can I describe it?
share|cite|improve this question
Where do the $k_1$ and $k_2$ suddenly come from? – Raskolnikov Mar 14 '11 at 21:37
OK, for the solution to be right $k_1=C_1-C_2$ and $k_2=-(C_1+C_2)$. (Although some multiple would work as well.) My suggestion: invert the Lambert W function. – Raskolnikov Mar 14 '11 at 21:44
Sorry, I fixed the question. – Helium Mar 14 '11 at 21:47
Thanks a lot. I solved the first part then. Since $W_0(f(y)) = 1 - x$, we can say $(1 - x)e^{1 - x} = f(y)$. We do the same thing with the other equation and the rest is straightforward. But I am still confused. Why I got a hyperbola as an answer instead of a point? Did we lost something? I mean a part of the information from the equations? – Helium Mar 14 '11 at 23:13
Yes, you combine the two equations into one, thereby you still have one independent equation to use. So you could for example pick one of the original equations and keep it. – Raskolnikov Mar 14 '11 at 23:16

$$\begin{cases} 1-x = W_0(\frac{C_1 e^{y + 1}}{y + 1}) \\ 1-y = W_0(\frac{C_2 e^{x + 1}}{x + 1}) \end{cases}$$ Using the poperty of the Lambert function $Y=W(X)$ invertion : $Ye^Y=X$ $$\begin{cases} (1-x)e^{1-x}=\frac{C_1 e^{y + 1}}{y + 1} \\ (1-y)e^{1-y}=\frac{C_2 e^{x + 1}}{x + 1} \end{cases}$$ $$C_1C_2e^{x+y}=C_2(1-x)(y+1)=C_1(1-y)(x+1)$$ $$C_2(1-x)y+C_1(x+1)y= C_1(x+1)-C_2(1-x)$$ $$y=\frac{C_1(x+1)-C_2(1-x)}{C_2(1-x)+C_1(x+1)}$$ This leads to the expected relationship : $$y=\frac{(C_1+C_2)x+C_1-C2}{(C_1-C_2)x+C_1+C_2}$$ Then we have to separate the equation with unknown $x$ from the equation with unknown $y$. $$y+1= \frac{2C_1(x+1)x}{ (C_1-C_2)x+C_1+C_2}$$ $$(1-x)e^{1-x}= \frac{C_1 e^{y + 1}}{y + 1} =\frac{C_1 e^{\frac{2C_1(x+1)x}{ (C_1-C_2)x+C_1+C_2}}}{\frac{2C_1(x+1)x}{ (C_1-C_2)x+C_1+C_2}}$$ $$2x(x+1)(1-x)e^{1-x}=((C_1-C_2)x+C_1+C_2) e^{\frac{2C_1(x+1)x}{ (C_1-C_2)x+C_1+C_2}}$$ This equation contains the unknown $x$ only. A similar one can be found containing $y$ only. But, the more likely, those equations cannot be solved for the unknown expressed on closed form.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.